Development of granular urea-zeolite slow release fertilizer using inclined pan granulator - Pisey Hoeung; Yazid Bindar; Samuel Pati Senda (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2011)
Slow release fertilizers (SRFs) are so crucial in improvement of agriculture productions. To increase urea fertilizer effectiveness and efficiency, the product could be modified in the form of SRFs. The objective is to conduct slow release urea fertilizer. During granulation, particle sizes of urea and natural zeolite mixture (50, 60 and 80 mesh), binder solution with different percentage (2% to 10%) of starch, and clay additives (5%, 7.5%, and 10%) were used. The obtained granule was further analyzed using percolation reactor to determine the slow release rate. Leachate from reactors was collected, by using UV-visible spectrophotometric method, concentration of dissolved urea was determined. The granule size of 3-4 mm, the urea-zeolite mixture particle size of 60-mesh, the percentage of clay addition in the granulation process of 7.5%, the percentage of starch addition in binder solution of 3% are selected to be the best in term of the roughness of the granules, economic aspects, and slow release rate. In addition, it is proportionally defined the release time of nutrient from experiment and from simulated program is at least for three months which is plenty of time for crops, especially for rice. Key words: Slow Release Fertilizer, Zeolite, Urea, Inclined pan granulatorAbstrakSlow release fertilizers (SRFs) memiliki peranan yang sangat penting dalam peningkatan produksi pertanian. Untuk meningkatkan efisiensi dan efektifitas pupuk urea, produk pupuk bisa dimodifikasi dalam bentuk SFRs. Tujuan dari penelitian ini adalah untuk membuat slow release urea fertilizer. Selama proses granulasi, digunakan ukuran partikel campuran urea dan zeolit alam (50, 60 dan 80 mesh), cairan perekat dengan persentase yang berbeda (2% sampai 10%) starch, dan tambahan tanah liat (5%, 7,5%, dan 10%). Butiran-butiran (granul) yang diperoleh selanjutnya dilakukan analisis menggunakan reaktor perkolasi digunakan untuk menentukan laju slow release. Leachate dari reaktor dikumpulkan, kemudian konsentrasi urea terlarut dapat diketahui dengan menggunakan metode spektrofotometri UV-Vis. Granul 3-4 mm, ukuran 60 mesh campuran antara urea dan zeolit, persentasi penambahan tanah liat dalam proses granulasi sebesar 7,5%, dan persentasi penambahan starch dalam larutan perekat sebesar 3% menunjukkan hasil yang terbaik untuk tingkat kekasaran butiran, aspek ekonomi dan menunjukkan pelepasan nutrisi lambat. Secara proporsional dapat dikatakan bahwa waktu pelepasan nutrisi yang diperoleh dari percobaan dan simulasi program, setidaknya untuk tiga bulan sangat cukup untuk tanaman, khususnya untuk padi.Kata kunci: Slow release fertilizers, Zeolit, Urea, granulator panci miring.